Династія качанівських благодійників - Половець, В. (Сiверянський лiтопис, 2018)
У статті досліджується життя та діяльність визначних представників династії качанівських благодійників – Григорія Степановича, Василя Васильовича (старшого) і Василя Васильовича (молодшого) Тарновських. Як особистості вони були різними, але, володіючи унікальними рисами характеру, життєвим досвідом і суспільними досягненнями, удостоїлися честі бути вписаними в історію, завдяки чому згадуються через століття. В статье исследуется жизнь и деятельность выдающихся представителей династии качановских благодетелей – Григория Степановича, Василия Васильевича (старшего) и Василия Васильевича (младшего) Тарновских. Как личности они были разными, но, владея уникальными чертами характера, жизненным опытом и общественными достижениями, удостоились чести быть вписаными в историю, благодаря чему вспоминаются через столетия. History of Chernihivshyna (Chernihiv area) keeps memory of many outstanding people who are related to Kachanivka. Kachanivka was a home place for Fedir Kachanivsky, the singer of the Russian Tsar’s court. It was the residence of P. Rumiantsev-Zadunayskyi, the President of Malorossiya Kollegium. Since 1827, this mansion had been the landowners Tarnovskyis’ country estate for three generations. Hryhoryi Tarnovsky (1786-1853) was the first of them by whose efforts Kachanivka turned into an attractive aristocratic mansion. As a patron of young talents, he built a collection of works of high artistic value. He was an honorary member of the Academy of Fine Arts. Under his will, his older cousin Vasyl Tarnovsky, Sr. (1810-1866) inherited the mansion. Vasyl had University degree and from his student’s years was interested in sciences. Among his academic works, the most important is “On Selfdom in Russia and Need to Remove It.» He was actively involved in civil events and provided considerable support to painters and writers. Kachanivka was inherited by his elder son Vasyl Tarnovsky, Jr. (1838-1899) and then reached its full splendor. Vasyl Tarnovsky, Jr. was fully giving himself to collecting art objects, doing charity and patronship work. He was engaged in numerous important events in Ukraine: made considerable contributions for erection of the monuments to Bohdan Khmelnytskyi in Kyiv and Ivan Kotlyarevskyi in Poltava, participated in editing the “Kievskaya Starina» (Kyiv Antiquity) magazine, arranging the tomb of Taras Shevchneko in Kaniv, etc. He spent the last years of his life in Kyiv where he is buried. So, thanks to the Tarnovskyis, the philanthropists, Kachanivka went down in history of Chernihivshchyna as an important cultural center, center where they collected pieces of art and patronized fine art and literature. Thanks to the Tarnovskyi family, a beautiful landscape park was built in Kachaivka that added to Kachanivka as an architectural and artistic gem. Thanks to these philanthropists Chernihiv has the collection of Ukrainian antiquities now and Ukraine has National museum of Taras Shevchenko.